Assessing cognitive processes related to insomnia: A review and measurement guide for Harvey's cognitive model for the maintenance of insomnia. (October 2015) - Hiller, Rachel M.; Johnston, Anna; Dohnt, Hayley; Lovato, Nicole; Gradisar, Michael
Summary: Cognitive processes play an important role in the maintenance, and treatment of sleep difficulties, including insomnia. In 2002, a comprehensive model was proposed by Harvey. Since its inception the model has received >300 citations, and provided researchers and clinicians with a framework for understanding and treating insomnia. The aim of this review is two-fold. First, we review the current literature investigating each factor proposed in Harvey's cognitive model of insomnia. Second, we summarise the psychometric properties of key measures used to assess the model's factors and mechanisms. From these aims, we demonstrate both strengths and limitations of the current knowledge of appropriate measurements associated with the model. This review aims to stimulate and guide future research in this area; and provide an understanding of the resources available to measure, target, and resolve cognitive factors that may maintain chronic insomnia.